Controlling schools: how school resource officers’ roles map onto schools’ behavior management strategies - Benitez, Ivan (Crime & delinquency, 2022)
School resource officer (SRO) behavior varies across schools, but little is known about what shapes their behavior. Social ecological theories state that features of communities shapes individual behavior, including police officers. This may similarly apply to SROs. This study uses the 2015 to 2016 School Survey on Crime and Safety to test the extent to which three aspects of a school’s context related to behavior management (i.e., security measures, disciplinary environment, and restorative practices) shape SROs’ involvement in three roles: law enforcement, teacher, and mentor. Using a generalized structural equation model to examine the relationships between school context and SRO roles, consistent with ecological theories, we find that school context shapes SRO roles. Implications and future research are further discussed.